Case Report: A case of functional reconstruction of second metacarpal following complex trauma with free fibula flap and silicone arthroplasty - Brambullo, Tito; Caporali, Enrico; Ricci, Federico; Vindigni, Vincenzo; Bassetto, Franco (Frontiers in Surgery, 2025)
Complex metacarpal fractures with segmental bone loss and joint involvement pose significant challenges for the hand trauma surgeon. When traditional techniques are inadequate, microsurgical reconstruction and joint arthroplasty may offer a viable alternative. We report the case of a 32-year-old male who sustained a high-energy injury to the right hand, resulting in a comminuted fracture of the second metacarpal head and extensive dorsal soft tissue loss. After initial management, reconstruction of the second metacarpal was performed using a free osteocutaneous fibula flap. Although the vascularized bone graft was sculpted to settle in the metacarpophalangeal joint, mobility was not preserved. A staged silicone MCP arthroplasty then was later performed to improve joint mobility. At 18 months follow-up, the patient showed good soft tissue coverage, restored grip strength and proximal interphalangeal joint motion, but improvement in MCP range of motion remained partial despite arthroplasty. This article highlights the potential and limitations of combining vascularized bone transfer with prosthetic joint replacement in high-demand patients following trauma.